The Impact of the Global Financial Crisison Microfinance and Policy Implications - Di Bella, Gabriel (IMF Working Papers; Working Paper ;, 2011)
The global financial crisis affected microfinance institutions (MFIs) as lending growth was constrained by scarcer borrowing opportunities, while the economic slowdown negatively impacted asset quality and profitability. It also brought to the fore the relatively high interest rates that MFIs charge to their (low-income) customers. This paper revisits the issue of systemic risk of MFIs, and finds that contrary to the evidence before the crisis, MFI performance is correlated not only to domestic economic conditions but also to changes in international capital markets. It also presents an empirical analysis of lending rates with the purpose of informing policy decisions, and finds that loan sizes, productivity, and MFI age contribute to explain differences in lending rate levels. This suggest that regulation (and policies) promoting MFI competition, and innovation in lending technologies have a better chance to result in decreased lending rates.